«The experience of fighting suffocation»: A somatic metaphor in late Soviet narratives of dissidence and emigration - G. S. Zelenina (Шаги)
The article examines the cluster of motives of air shortage, labored respiration, suffocation and strangling as one of the important topoi in autobiographical texts written by Soviet dissidents during the era of stagnation, including activists of the Jewish national movement who struggled for emigration from the Soviet Union. The topos has several variations in dissident discourse; it has a mirror parallel in pro-government discourse, i. e., the motive of purifying the air of the motherland by expelling foreign and hostile members of society who pollute it; it has a continuation in egodocuments written in emigration; and, finally, it may constitute a foundation in the deteriorating ecological reality and environmentalist rhetoric of the Soviet press which became increasingly conscious of environmental pollution during the 1970s. Besides such explanations as this topos being a possible reflection of environmental anxiety or a description of shortness of breath characteristic of depressive disorders to which some of the dissident authors were prone, it is assumed that the choice of this particular somatic metaphor among other possible ones in order to describe the unbearableness of living in the Soviet Union was primarily due to its very frequency, which led to a kind of suffocation epidemic and ensured the reproduction of the topos.